Heavy metals assessment of soils in and around Kama-Otto and Kwotto artisanal mining of mica, cassiterite and tantalite in Nasarawa state, Nigeria - Isa Osu, Usman; Edith Bolanle, Agbaji; Hadiza, Omenesa (International Journal of Advanced Chemistry, 2018)
This study assesses the level of heavy metal in Soils within the vicinity of artisanal mining of Mica, Cassiterite and Tantalite in Nasarawa State, Nigeria. Soil samples of Kama-otto and Kwotto artisanal mining were collected and analyzed using mass-plasma Atomic emission spectroscopy (MP-AES). Samples were also collected in Angwan-Mada, a non-artisanal mining environment, for comparison. Pollution assessment of soil samples using the following geochemical parameters such as contamination factor (CF), pollution load index (PLI), and Enrichment factor (EF), Nemerow index method (IIN) and Geo-accumulating index (Igeo) were carried out. The results indicate an elevation in pollution status in the order of Kama-otto mining, Kwotto mining, Kama-otto, Kwotto and Angwan-mada. The concentrations of Cd, Cr and Mn were significant in the sampled areas (P < 0.05).Â Â